New chrysanthemum varieties - Bala, Madhu (Indian Horticulture, 2019)
Chrysanthemum varieties, viz. Punjab Shingar and Punjab Mohini were released by the Punjab Agricultural University, Ludhiana in 2018. Punjab Shingar is floriferous variety with compact and upright growth habit. Flowers are decorative type, white in colour and suitable for loose flower purpose. Punjab Mohini is dwarf variety with compact growth habit, no pinch no stake variety. Flowers are single Korean type, white with yellow center and suitable for pot culture.